Final answer:
To rewrite expressions without negative exponents, use the rule that any number raised to the power of -n is equal to 1 divided by that number raised to the power of n. Apply this rule to each expression, following the steps provided.
Step-by-step explanation:
To rewrite without negative exponents, we use the rule that any number raised to the power of -n is equal to 1 divided by that number raised to the power of n. Applying this rule to the given expressions:
- a / b = a * b-1 = a * (1/b)1
- a x b = a * b1
- b / a = b * a-1 = b * (1/a)1
- b x a = b * a1
So, the expressions without negative exponents are:
- a / b = a * (1/b)
- a x b = a * b
- b / a = b * (1/a)
- b x a = b * a